Characterization of Mycoplasma penetrans and Mycoplasma fermentans immunodominant proteins Caracterização de proteinas imunodominantes de Mycoplasma penetrans e Mycoplasma fermentans - Juliana Bruder (Brazilian Journal of Microbiology, 2005)
Mycoplasmas are a heterogeneous group of the smallest organisms capable of self replication and are known to cause many detrimental diseases in both animals and humans. These wall-less prokaryotes are enveloped by a lipoprotein membrane and their small genomes are sufficient to synthesize molecules required for growth and self-replication. Among sixteen species isolated from humans, Mycoplasma pneumoniae, an agent of primary atypical pneumonia, and the urogenital tract species Mycoplasma hominis,Ureaplasma urealyticum and Ureaplasma parvum have been confirmed to be pathogenic. Mycoplasma penetrans and Mycoplasma fermentans, which are species associated with HIV, have been investigated mainly in research laboratories. In this study we have characterized lipid-associated membrane proteins (LAMP) of Mycoplasma penetrans and Mycoplasma fermentans, in view of the importance of mycoplasmas in human diseases and the peculiar antigenic variation observed in these species. To characterize proteins with possible diagnostic value, we used ELISA and Western blot in sera of pregnant women whose cervical samples were positive for these species of mycoplasmas when tested by PCR. ELISA showed IgG anti-LAMP-M. fermentans antibodies to be present in 57.5% of cases and IgM antibodies to be present in 74.5% of cases. The three samples that were PCR positive for M. penetrans showed IgG anti-LAMP-M. penetrans antibodies, and one sample was positive for IgM. No IgA antibodies against either species were detected in any of the samples. LAMP analysis by Western blot revealed the 35, 38, 42, 61 and 103 kDa proteins of M. penetrans and the 29, 38, 41, 61, 78 and 95 kDa proteins of M. fermentans. Among these, will be considered p35 to M. penetrans and 29 kDa protein to M. fermentans, the main immunoreactive proteins and therefore useful markers for further laboratory diagnosis. Micoplasmas são procariotos diminutos, desprovidos de parede celular e envoltos por uma membrana lipoproteica cujo pequeno genoma sintetiza a maioria das moléculas necessárias para crescimento e replicação. Dentre as dezesseis espécies isoladas do homem, Mycoplasma pneumoniae, agente causador da pneumonia atípica primária, e as espécies do trato urogenital como Mycoplasma hominis,Ureaplasma urealyticum e Ureaplasma parvum têm definido seu papel patogênico. M. penetrans e M. fermentans, espécies associadas ao HIV, têm sido investigadas principalmente em laboratórios de pesquisa. Considerando a importância dos micoplasmas nas doenças humanas e a peculiar variação antigênica observada em tais espécies, foram caracterizadas, neste estudo, as lipoproteínas associadas a membranas (LAMP) de Mycoplasma penetrans e Mycoplasma fermentans. Para definir peptídeos com possível valor diagnóstico, empregamos as técnicas de ELISA e de Western blot usando soros de gestantes cujas amostras cervicais foram positivas por PCR. Por meio do ELISA foram observados anticorpos IgG anti-LAMP-M. fermentans em 57,5% e IgM em 74,5% das amostras. As três amostras PCR positivas para M. penetrans apresentaram anticorpos IgG anti-LAMP-M. penetrans e uma amostra positiva para IgM. IgA não foi detectada em nenhuma das espécies. A análise da LAMP, por Western blot, revelou como principais proteinas imunoreativas: 35, 38, 42, 61 and 103 kDa para M. penetrans e 29, 38, 41, 61, 78 and 95 kDa de M. fermentans. Dentre estas podemos considerar p35 específica para M. penetrans e p29, M. fermentans.Tais proteinas são promissoras como marcadores em diagnóstico.